Fluid cavitation detection method with phase demodulation of ultrasonic signal. (January 2015) - Yan, Zhaoli; Liu, Jin; Chen, Bin; Cheng, Xiaobin; Yang, Jun
Abstract: Cavitation is a specific liquid dynamic phenomenon that usually occurs during the operation of hydraulic machinery. This phenomenon is a subject of great concern because it reduces mechanical efficiency, degrades and damages the surface of the propeller, and increases undesirable vibrations and noise emissions. These factors affect the service life and operational safety of hydraulic equipment. In this paper, a novel cavitation detection method with phase demodulation of ultrasonic signals is proposed. Firstly, the modulation of the fluid motion of the ultrasonic signal is analyzed. The algorithm describing the relationship between the ultrasonic phase and the spatial mean velocity of flow field is then investigated. Moreover, a classifier model based on support vector machine is established to identify the cavitation state. The performance of the proposed method is experimentally verified in the laboratory using 320 test samples. The successful recognition rate reaches 98%, which indicates good stability and accuracy for cavitation detection. The ultrasonic transducers are installed on the outer surface of the pipeline, which is believed to be more suitable for practical applications than hydroacoustics or other pressure and optical cavitation detection methods. Furthermore, the proposed method can be used to discriminate between laminar and turbulent flows in the pipeline.